First record of Bombylisoma Rondani (Diptera: Bombyliidae) from China and an identification key to the Chinese genera of Bombyliinae - Yao, Gang; Evenhuis, Neal L. (Zootaxa, 2016)
Bombylisoma Rondani is a genus of bee flies belonging to the subfamily Bombyliinae (Hull, 1973). It is easily identified by the following characters: Head usually as broad as thorax; hind-margin of eyes indented; wings often small, narrowed at base with at least alula reduced; hind femora often without macrochaetae; body usually more elongate even narrow conical or cylindrical, macrochaetae usually weak often hair-like especially those posterior to the wings; cell r5 open, pulvilli well-developed; male terminalia with gonocoxite without prominent crest; parameral sheath, bearing paired horn-like outgrowths (Greathead & Evenhuis, 2001). Bombylisoma includes two known species from the Oriental Region: B. ghorpadei Kapoor & Agarwal, 1979 and B. resplendens Brunetti, 1909 (Evenhuis & Greathead, 2015). No species has previously been reported from China. Recently, one specimen of Bombylisoma collected from Yunnan was found in the Bernice Pauahi Bishop Museum. In the present paper this species, B. resplendens Brunetti, is redescribed and this represents the first record of the genus from China. A key to the genera of the Bombyliinae from China is presented.